Phylogenetic Relationship among Grasses, Wheat and Pearl Millet using matK and rbcR Genes - Molla, M M H; Saha, M C; Serba, D; Talukdar, S K; Salam, M A; Ahmed, M Shahabuddin; Islam, M S (Plant Tissue Culture and Biotechnology, 2023)
Fourteen genotypes of tall fescue, Brachypodium, wheat and pearl millet were used to find out phylogenetic relationships at their different ploidy level. Isolated chloroplast DNA of the 14 genotypes was sequenced using some selected matK and rbcR genetic markers. The matK and rbcR chloroplast gene sequences length were 1539bp and 1431bp, respectively. The consensus sequence length of matK gene was 1265bp in Brachypodium and wheat, 1266bp in both tall fescue Continental and Mditerranean species, 1269bp in pearl millet and for rbcR gene was only 1156bp in all studied four species. Except in Brachypodium, the variations of SNP for both matK and rbcR genes were observed in different ploidy levels of pearl millet and between the tall fescue Continental and Mediterranean species. Wheat with their different ploidy level gave the SNP variations only for matK gene. In respect of all ploidy levels, pearl millet had the highest number of SNP for both matK (247) and rbcR (130) genes. The tall fescue Continental (129) and Mediterranean (123) were in second position to show their genetic variation for matK gene. The rbcR gene had higher SNP at 5¢ regions of all four species, but matK gene only in wheat and tall fescue and 3¢ in millet and Brachypodium species. There was no in-del for rbcR gene, but the insertion of nucleotide for the matK gene was found highest in diploid wheat (11) and the deletion was in pearl millet (6). The phylogenetic analysis stated that their relationships were tall fescue Continental and tall fescue Mediterranean was much more related to wheat than pearl millet and Brachypodium. Plant Tissue Cult. & Biotech. 33(1): 57-70, 2023 (June)